Skin autofluorescence is associated with past glycaemic control and complications in type 1 diabetes mellitus - Genevieve, M.; Vivot, A.; Gonzalez, C.; Raffaitin, C.; Barberger-Gateau, P.; Gin, H.; Rigalleau, V. (Diabetes & metabolism, 2013)
As skin autofluorescence (AF) can assess subcutaneous accumulation of fluorescent advanced glycation end-products (AGEs), this study aimed to investigate whether it was linked to glycaemic control and complications in patients with type 1 diabetes mellitus (T1DM). Using the AGE Reader™, AF was measured in T1DM patients referred to Haut-Levêque Hospital (Bordeaux, France); data on their HbA1c levels measured every 6months as far back as the last 5years were also collected. The association of AF with the patients’ past glucose control, based on their latest HbA1c values, and the means of the last five and 10 HbA1c values, and with diabetic complications was also examined by linear regression analysis. The sample included 300 patients: 58% were male; the mean age was 49 (SD 17) years and the mean diabetes duration was 21 (SD 13) years. The median skin AF measurement was 2.0 [25th–75th percentiles: 1.7–2.4] arbitrary units (AU), and this was associated with age (β=0.15 per 10years, P<0.001) and diabetes duration (β=0.17 per 10years, P<0.001). After adjusting for age and estimated glomerular filtration rate (eGFR), the skin AF measurement was also related to the means of the last five and 10 HbA1c values (β=0.10 per 1% of HbA1c, P=0.005, and β=0.13 per 1% of HbA1c, P=0.001, respectively). In addition, the skin AF was associated with retinopathy (P<0.001), albuminuria (P<0.001) and decreased eGFR (P<0.001). In conclusion, the skin AF is related to the long-term glucose control and diabetic complications. L’autofluorescence cutanée pouvant évaluer l’accumulation des produits fluorescents de glycation avancée, l’objectif de notre étude était d’analyser son association avec le contrôle glycémique et les complications des patients présentant un diabète de type 1. En utilisant l’AGE Reader™, nous avons mesuré l’autofluorescence cutanée chez les patients ayant un diabète de type 1 suivi tous les sixmois sur cinqans à l’hôpital Haut-Levêque (Bordeaux, France). Nous avons étudié sa relation avec le contrôle glycémique: la dernière HbA1c, la moyenne des cinq et dix dernières HbA1c, et avec l’existence de complications, par régression linéaire. Les 300 patients (58 % d’hommes) avaient une moyenne d’âge de 49±17ans et une durée de diabète moyenne de 21±13ans. L’autofluorescence cutanée médiane était de 2,0 [1,7–2,4] unités arbitraires (UA), associée à l’âge et à la durée de diabète (β=0,15 pour 10ans, P<0,001 et β=0,17 pour dixans, P<0,001). Après ajustements pour l’âge et le débit de filtration glomérulaire estimé (DFGe), elle était liée à la moyenne des cinq dernières HbA1c (β=0,10 pour 1 % d’HbA1c, P=0,005) et des dix dernières HbA1c (β=0,13 pour 1 % d’HbA1c, P=0,001). L’autofluorescence cutanée était associée avec la présence d’une rétinopathie diabétique (P<0,001), d’une micro- ou macroalbuminurie (P<0,001) et d’une réduction du DFGe (P<0,001). L’autofluorescence cutanée est liée au contrôle glycémique à long terme et aux complications (néphropathie et rétinopathie) chez les patients présentant un diabète de type 1.